Síntese de β-enaminonas e aminopirazóis trifluormetilados - Goulart, Taís Barcelos (2017)
In the present work a systematic series of eight-aminopyrazoles trifluoromethylates was synthesized by conventional methodology in three reactional steps. The first step is to obtain the compound 1,1,1-trifluoro-4,4-diethoxy-3-buten-2-one (97%) by reaction with triethylorthoacetate, trifluoroacetic anhydride, pyridine as the base and in chloroform solvent. Subsequently these were used as starting materials in reactions with eleven different amines, where (4-(2-aminoethyl)morpholine, N-(3-aminopropyl)piperidine, (aminomethyl)cyclohexane, 2-(aminomethyl)furan, 3-(aminomethyl)pyridine, 2-(aminomethyl)pyridine, 2-aminopyridine, 1-(2-aminoethyl)piperidine, 1-(2-aminoethyl)pyrrolidine, 1-(2-aminoethyl) piperazine and N, N-diethylpropane-1,3-diamine), the second reaction step was carried out in acetonitrile at room temperature over a period of 18 hours to form 4-amino-4-ethoxy-1,1 , 1-trifluorobut-3-en-2-ones (β-enaminones) in good yields (60-97%). The latter step consists in the formation of the Pirazol trifluoromethylated by reacting the β-enaminones with the hydrazine dihydrochloride, triethylamine as the base in ethanol as the solvent at a temperature of 78 ° C over a period of 48 hours in yields of (50-84%). NMR and GC/MS In this way, eighteen novel trifluoromethyl compounds were obtained in the literature structures were by NMR1H e 13C e GC/MS.